ä½¿ç”¨æ‰‹åŠ¿æ³•æé«˜é«˜ä¸ä¸€å¹´çº§çš„å¦ç”Ÿå¯¹ å£°æ¯çš„æŽŒæ¡èƒ½åŠ› - Sedtyarum, Wiska; Thamrin, Lily; ., Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
??????????????????????????????????????????????????????????????????????????????????TARUNA BUMI KHATULISTIWA??????????????????????zh?ch?sh?z?c?s???????????????????????????????????????????zh?ch?sh?z?c?s????????? ? ??????? ?? ??? Abstract: Pronunciation is the first step in language learning,because pronunciation can not be seperated in every language. In Mandarin, consonant being one of the problem. Consonant zh, ch, sh and z, c, s are the most fault that students do. Students grade X in SMA Taruna Bumi Khatulistiwa also have the some problem, because of that the writer uses the hand movement method is good. The students being more spirit . that makes the ability in pronunce zh, ch, sh and z, c, s better .